Money - Ramsden, Peter; British Broadcasting Corporation. Television Service (Milton Keynes : Open University)
Discusses about money and power and also the monetary policy
Converted into VHS 1/2 in. and U-matic
Title from title screen
Executive producer, Alan Hancock ; graphic, Rosemary Held
Speaker : F.S. Brooman
Keywords: Money; Monetary policy